THE TRAM-FPV RACING Open Database. Sequences complete indoor flight tests for the study of racing drones - Castiblanco Quintero, Jose M.; Garcia-Nieto, Sergio; Ignatyev, Dmitry; Blasco, X. (University of Rioja, 2022)
This paper presents the TRAM-FPV Racing open database, generated from a set of indoor flights performed with five racing drones at Cranfield University (UK), specifically at the Flight Arena, one of the largest indoor flight fields in the world for research purposes. The database incorporates the position and orientation information in the space of five racing drone models using an optical measurement system (OMS). It includes readings from accelerometers, gyroscopes, and heading angles recorded by inertial unit (IMU) sensors. These databases are frequently used to develop and adjust the sensor fusion algorithms incorporated in the drones to estimate their current state vector. However, their field of application is vast, being able to be used, for example, for the development of the nonlinear mathematical models of drones or the generation of trajectories.